2023
DOI: 10.24857/rgsa.v17n7-017
|View full text |Cite
|
Sign up to set email alerts
|

Social Development Strategies of English as Second Language Learners for International Management

Samah Abduljawad

Abstract: Purpose: The goal of the current study is to investigate how English as a second language or English as a foreign language learners use teaching methodologies and to pinpoint any potential risk factors.   Theoretical framework: This research investigates whether elements like English language competency, academic success, learner environment, enthusiasm, psychology, etc. may be linked to the usage of study techniques by students who do not speak English as their first language.   Methods: The learning strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Curry and Wergin (1993) emphasized that the professional holds special social importance and social responsibilities as well. Moreover, many researchers have shown that pursuit of profit is an indispensable aspect of the professional, in that the primary purpose of most professional activities includes earning a living (Abduljawad, 2023;Bickham, 1998;Curry & Wergin, 1993;Houle, 1980;Nowlen, 1990;Schein, 1972;Sukendro, Riyanto, Karwanto, & Hartono, 2023;Wilensky, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Curry and Wergin (1993) emphasized that the professional holds special social importance and social responsibilities as well. Moreover, many researchers have shown that pursuit of profit is an indispensable aspect of the professional, in that the primary purpose of most professional activities includes earning a living (Abduljawad, 2023;Bickham, 1998;Curry & Wergin, 1993;Houle, 1980;Nowlen, 1990;Schein, 1972;Sukendro, Riyanto, Karwanto, & Hartono, 2023;Wilensky, 1964).…”
Section: Introductionmentioning
confidence: 99%